2023
DOI: 10.3389/fneur.2023.1152052
|View full text |Cite
|
Sign up to set email alerts
|

Presence of corrective saccades in patients with normal vestibulo-ocular reflex gain in video head impulse test

Abstract: BackgroundThe video head impulse test (vHIT) is a valuable clinical tool that can help identify dysfunction of the semicircular canals. While in cases with semicircular canal dysfunction, both decreased vestibulo-ocular reflex (VOR) gain and corrective saccades (CS) are usually observed, there are cases which show CS despite normal VOR gain in vHIT.ObjectiveThis study aimed to investigate the clinical characteristics of patients who showed CS with normal VOR gain in vHIT.Materials and methodsAmong 390 patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…However, other studies have suggested that the presence of free otoliths can affect the results of vHIT ( 4 , 14 , 15 ). In this study, most of the abnormal vHITs of BPPV were normal gain with saccades, which can be considered as a relatively light degree of semicircular canal injury ( 8 , 16 , 17 ). Comparing the proportion of saccades between groups, only the proportion of HC saccades in the pc-ca group was higher than that in the control group, and there was no difference between the healthy side and the affected side within the group, which also suggested that there is a lack of correlation between abnormal vHIT and the responsible semi-regulation of bppv.…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…However, other studies have suggested that the presence of free otoliths can affect the results of vHIT ( 4 , 14 , 15 ). In this study, most of the abnormal vHITs of BPPV were normal gain with saccades, which can be considered as a relatively light degree of semicircular canal injury ( 8 , 16 , 17 ). Comparing the proportion of saccades between groups, only the proportion of HC saccades in the pc-ca group was higher than that in the control group, and there was no difference between the healthy side and the affected side within the group, which also suggested that there is a lack of correlation between abnormal vHIT and the responsible semi-regulation of bppv.…”
Section: Discussionmentioning
confidence: 65%
“…The following conditions are considered abnormal in vHIT: (1) horizontal semicircular gain <0.8, vertical semicircular gain <0.7 ( 6 ), accompanied by CS. (2) normal gain, with CS in more than 50% of trials, i.e., the ratio of CS is over 50% ( 7 , 8 ).…”
Section: Methodsmentioning
confidence: 99%
“…Intuitively, it can be inferred that the amplitude of the compensatory overt saccade (i.e., the saccadic velocity) is proportional to the degree of weakness of the VOR, i.e., more the weakness, more is the amplitude of the saccade ( 4 ). Furthermore, it has emerged that in compensating vestibular weakness, the VOR gain might recover without saccades ( 5 ), but saccades may also persist ( 6 ) due to prolonged central adjustment regulating mechanisms.…”
Section: Introductionmentioning
confidence: 99%